Systemic Administration of Fibroblast Growth Factor 21 Improves the Recovery of Spinal Cord Injury (SCI) in Rats and Attenuates SCI-Induced Autophagy - Zhu, Sipin; Ying, Yibo; Ye, Lin; Ying, Weiyang; Ye, Jiahui; Wu, Qiuji; Chen, Min; Zhu, Hui; Li, Xiaoyang; Dou, Haicheng; Xu, Huazi; Wang, Zhouguang; et al. (Frontiers in Pharmacology, 2021)
Protecting the death of nerve cells is an essential tactic for spinal cord injury (SCI) repair. Recent studies show that nerve growth factors can reduce the death of nerve cells and promote the healing of nerve injury. To investigate the conducive effect of fibroblast growth factor 21 (FGF21) on SCI repair. FGF21 proteins were systemically delivered into rat model of SCI via tail vein injection. We found that administration of FGF21 significantly promoted the functional recovery of SCI as assessed by BBB scale and inclined plane test, and attenuated cell death in the injured area by histopathological examination with Nissl staining. This was accompanied with increased expression of NeuN, GAP43 and NF200, and deceased expression of GFAP. Interestingly, FGF21 was found to attenuate the elevated expression level of the autophagy marker LC3-II (microtubules associated protein 1 light chain 3-II) induced by SCI in a dose-dependent manner. These data suggest that FGF21 promotes the functional recovery of SCI via restraining injury-induced cell autophagy, and hint that systemic administration of FGF21 could have a therapeutic potential for SCI repair.